Developing Storylines of Plausible Future Streamflow and Generating a New Warming‐Driven Declining Streamflow Ensemble: Colorado River Case Study - Homa Salehabadi; David G. Tarboton; Kevin Wheeler; James Prairie; Rebecca Smith; Sarah Baker (Water Resources Research)
Abstract Plausible future streamflow time series are essential for evaluating policies and management strategies in river basins and testing the operation of water resource systems. Relying solely on stationary historical data is not sufficient in a changing climate. However, uncertainty in the range of streamflow projections from General Circulation Models calls into question their direct use in water resources planning. An intermediate approach is needed to identify ensembles of streamflow time series based on well‐defined assumptions that represent plausible future hydrologic conditions. This paper suggests multiple quantitative storylines of plausible future conditions, each matched with a representative streamflow ensemble to serve as inputs for planning models where, to account for uncertainty, plans or policies that are robust to a range of plausible futures are developed. Applying this approach in the Colorado River Basin we found that, while three storylines were well matched with existing ensembles, there was no suitable ensemble representing increasing variability around a declining mean. To address this gap, we developed a general method to create new streamflow ensembles that account for future changes by combining observed and paleo‐reconstructed flows and adjusting the marginal distribution of the streamflow time series to incorporate the estimated decline in, and increasing variability of, future flow. The results are a set of quantitative storylines that justify a range of plausible future conditions, and a new warming‐driven declining streamflow ensemble for use in Colorado River Basin scenario evaluation and decision‐making representing the plausible increasing variability around a declining mean storyline.